iPSC screening identifies CACNA2D2 as a potential therapeutic target for FTLD-Tau - Keiko Imamura; Ayako Nagahashi; Aya Okusa; Tomoki Sakasai; Kayoko Tsukita; Yumiko Kutoku; Yutaka Ohsawa; Yoshihide Sunada; Naruhiko Sahara; Nicholas M. Kanaan; Makoto Higuchi; Kohji Mori; et al. (European Journal of Cell Biology)
Frontotemporal Lobar Degeneration (FTLD) is a neurodegenerative disorder that affects the frontal and temporal lobes, which are crucial for regulating personality, behavior, and language. Pathologically, FTLD is characterized by Tau protein accumulation and neuronal death. In our effort to identify disease-modifying treatments, we conducted drug screening using neurons derived from induced pluripotent stem cells (iPSCs) of FTLD-Tau patients. This screening identified gabapentin as an existing drug that suppresses neuronal cell death with suppressed accumulation of Tau oligomers. Treatment with gabapentinoids, including pregabalin and mirogabalin, demonstrated similar neuroprotective effects. These compounds bind to the α2δ subunit of voltage-dependent calcium channels and specifically target the two isoforms α2δ-1 and α2δ-2. To determine which isoform is involved in the neurodegeneration seen in FTLD-Tau, we employed a knockout approach using iPSCs, which revealed that α2δ-2, encoded by CACNA2D2, plays a key role in the degeneration of FTLD-Tau neurons. Moreover, Neural organoids of FTLD-Tau exhibited features indicative of neurodegeneration, and CACNA2D2 knockout reversed a part of the gene expression alterations associated with these neurodegenerative features. These findings suggest that α2δ-2 may be a promising target for disease-modifying therapies in FTLD-Tau.